2007
DOI: 10.1159/000113490
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Expression and Its Prognostic Significance in Colorectal Cancer

Abstract: Objective: The extracellular matrix glycoprotein tenascin-C has been proposed as a tumor marker with prognostic significance in many cancer forms, but in colorectal cancer, reported results have been controversial. The aim of this study was to evaluate the prognostic value of immunohistochemical tenascin-C expression in a series of 231 patients with colorectal cancer. Methods: Paraffin-embedded formalin-fixed specimens were stained with a tenascin-C-specific monoclonal antibody, and the stromal staining intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Tenascin expression is highly upregulated during tumor invasion in many tumor types, including colorectal carcinomas [24]. In the present study we found a borderline relationship of TSP-1 expression with TN (p=0.053).…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Tenascin expression is highly upregulated during tumor invasion in many tumor types, including colorectal carcinomas [24]. In the present study we found a borderline relationship of TSP-1 expression with TN (p=0.053).…”
Section: Discussionsupporting
confidence: 40%
“…In infiltrating CRC, TN is expressed in the stroma and appears to be associated with progressive disease and poor prognosis [23]. FN is regarded as the major mesenchymal ECM glycoprotein involved in cell-matrix and cell-cell adhesion, cell migration, morphogenesis, differentiation, and oncogene transformation [24]. In CRC, FN immunostain shown a strong expression and different distribution compared with normal colorectal tissue [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No fibronectin was detected in MCF-7 or MDA-IBC-3 mammospheres. Tenascin-C is expressed in the stroma of tumors and is associated with a poor prognosis [20], [21]. Tenascin-C binds to fibronectin and can reduce cell adhesion in vitro [22].…”
Section: Resultsmentioning
confidence: 99%
“…TN‐c appeared in the ECM as a continuous line or as reticulate yellow grains. The level of immunoreactivity was expressed by scoring the intensity of TN staining (2). No color or light staining was considered negative, while yellow or yellow‐brown staining was considered positive.…”
Section: Methodsmentioning
confidence: 99%